Overexpression of Gremlin1 in Mesenchymal Stem Cells Improves Hindlimb Ischemia in Mice by Enhancing Cell Survival. Issue 5 (20th December 2016) - Xiang, Qiuling; Hong, Dongxi; Liao, Yan; Cao, Yong; Liu, Muyun; Pang, Jun; Zhou, Junjie; Wang, Guang; Yang, Renhao; Wang, Maosheng; Xiang, Andy Peng
Abstract : Mesenchymal stem cells (MSCs) are a promising cell resource for the treatment of ischemic diseases, partially through paracrine effects. One of the major obstacles of MSC treatment is the poor survival rate and low efficiency of transplanted stem cells due to ischemic or inflammatory environments. Gremlin1 (GREM1), a regulator of growth, differentiation and development, has been identified as a novel proangiogenic factor. However, the role and mechanism of GREM1 in MSCs remains unclear. Therefore, we assessed the putative beneficial effects of GREM1 on MSC‐based therapy for hindlimb ischemia. The lentiviral vector, EF1a‐GREM1, was constructed using the Multisite Gateway System and used to transduce MSCs. In vitro studies demonstrated increased survival of GREM1‐MSCs exposed to H2 O2, which is consistent with the activation of caspase‐3. Conditional medium from GREM1‐MSCs (GREM1‐MSC‐CM) increased the anti‐apoptotic effects of human umbilical vein endothelial cells (HUVECs), and this effect was attenuated by treatment with the PI3K/Akt pathway inhibitor LY294002. MSCs modified with GREM1 could significantly increase blood perfusion of the ischemic hindlimb in vivo in a mouse model, which was correlated to improved MSC survival. This study demonstrates that overexpression of GREM1 in MSCs have greater therapeutic effects against ischemia compared with wild‐type MSCs by enhancing the survival of MSCs and ECs, which may provide new tools for studies investigating the treatment of ischemic diseases. J. Cell. Physiol. 232: 996–1007, 2017. © 2016 Wiley Periodicals, Inc. Abstract : This study demonstrates that overexpression of GREM1 in MSCs have greater therapeutic effects against ischemia compared with wild‐type MSCs by enhancing the survival of MSCs and ECs, which may provide new tools for studies investigating the treatment of ischemic diseases.